Bank audit - Adewunmi, Wole (Lagos: University of Lagos Press, 1992)
Bank audit is a compilation of papers from a national seminar sponsored by Continental Merchant Bank Nigeria Plc. The book contains articulate views of senior banking executives, seasoned practitioners in the field of auditing and chief executives in the government regulatory agencies. It covers the entire spectrum of bank audit and serves as a guide in the effective management of bank operations.
Loans
rua 07/11/16
Keywords: Bank examination; Bank management; Bank audit; Nigeria